PENGARUH KUALITAS PRODUK DAN VARIASI PRODUK TERHADAP MINAT BELI KONSUMEN (STUDI KASUS GREEN ARGOPURO KECAMATAN SUMBERMALANG) - solihah, raidatus; Fahrudin (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This research has the aim of knowing the effect of product quality and variety on consumer buying interest in green argopuro, Sumbermalang sub-district. This study used a sample of 60 consumers. The data analysis method used is multiple linear regression analysis. The results obtained in this study indicate that product quality has a significant effect on buying interest (Y) with a t-count value of 2.937 and t-table 2.002 which means t-count is greater than t-table and singnifikasinya 0.004 produl variations have a significant effect on consumer buying interest with a t-count value of 5.507 and t-table 2.002 and a significance value of 0.000. And the variables of product quality and product variety simultaneously have a significant influence on consumer buying interest in green argopuro, Sumbermalang sub-district with the F value obtained is 74.371 which is greater than f table 3.16 and a significance value of 0.000 which is smaller than 0.05. The conclusion of this study is that the variable quality and variety of products have a significant influence partially or simultaneously on consumer buying interest in green argopuro sub-district Sumbermalang. Keywords: product quality, product variety, purchase intention